Prevalence and predisposition to deep vein thrombosis in professional male soccer players - Drobnic, F.; de Suso, J. M. G.; Turmo-Garuz, A.; Gudelis, M.; Valle, X.; Peirau, X.; Souto, J. C.; Escudero, J. R.; Soria, J. M. (Apunts Sports Medicine, 2021)
The long recovery time required after deep venous thrombosis (DVT), or other serious manifestations of venous thromboembolic disease, can lead to a reduction in sporting condition and economic losses. Neither are such events always free of clinical sequelae. Objective: This study examines the prevalence of DVT in male, professional soccer players in Spain. Methods: A questionnaire on DVT events experienced by players in the ongoing 2015-16 season, and the previous 10 seasons, was sent to the medical services of all first and second division clubs in Spain. The genetic predisposition of those who suffered an event was investigated using the inCode thrombus test, as well as in 73 players who experienced no such event. Results: Four subjects were diagnosed with DVT via clinical history and ultrasound or D-dimer determination. This associated prevalence (1.2/1000) is higher than reported (1/10,000) for this age group in the general population (18-35 years). All four affected players carried a risk allele (A1) at the ABO locus, three were homozygous for the risk allele of FactorXIII, and one was heterozygous for a risk allele of FactorXII. Among the 73 players who experienced no DVT, 3 high risk genetic variants associated with thromboembolic events were detected in 7 players (9.6%), either in the SERPINA_A10, FactorV, FactorXII, or FactorXIII genes. Conclusion: DVT prevalence in professional soccer players is higher than expected for the same age segment, and highlights how genetic predisposition towards thromboembolic processes and sport-associated environmental risk factors work in tandem in the DVT appearance.